Associations of perceived neighbourhood and home environments with sedentary behaviour among adolescents in 14 countries: the IPEN adolescent cross sectional observational study - Ranjit Mohan Anjana; Harish Ranjani; Ester Cerin; Muhammad Akram; Jo Salmon; Terry L. Conway; Kelli L. Cain; Rajendra Pradeepa; Anthony Barnett; Cindy H. P. Sit; Delfien Van Dyck; Adriano Akira Hino; et al. (BMC, 2024)
Abstract Background Understanding environmental correlates of sedentary behaviour (SB) among young people is important as such data can identify approaches to limit sedentary time. This paper estimates associations of parent-reported neighbourhood and adolescent-reported home environments with SB among adolescents aged 11-19 years from 14 countries. Methods In the International Physical activity and the Environment Network (IPEN) Adolescent Study (an observational, cross-sectional multi-country study), adolescents wore a triaxial accelerometer for seven days that assessed sedentary time (ST). Adolescents completed survey measures of sedentary behaviour (SB) related to recreational screen time and sitting time in motor vehicles. Parents and adolescents completed surveys assessing neighbourhood and home environments. Accelerometer based ST was available in 3,982 adolescents while survey data were available for 6,302 dyads. We estimated the total and direct effects of each environmental attribute on ST and SB. Sex of the adolescent and city/country were examined as moderators. Results The average ST in adolescents from 14 countries ranged from 7.8 to 10.5 h/day. Personal social media was the only significant correlate of total ST across both sexes. With respect to self-reported SB, adolescents accumulated an average of 3.8 h of non-school screen time per day and nearly 40 min of transport-related sitting time. Screen time was associated with all home environment variables, including social media account, as well as land use mix-diversity, traffic safety, and crime safety. Transport-related sitting time was related to land use mix-diversity, recreation facilities, walking facilities, and pedestrian infrastructure, but no home environment variables. City/country and sex were significant moderators of several associations. Conclusions Both home and neighbourhood environment features were related to ST and SB. Having social media accounts emerged as a major contributor towards sedentarism in adolescents.